A Rare Cause of Acquired Factor X Deficiency in an 87-Year-Old Female - Ayrton Bangolo; Trupti Waykole; Bilal Niazi; Chandini Sajja; Mahabuba Akhter; Bhavna Gupta; Sameh Elias (Case Reports in Hematology)
Factor X deficiency is a rare coagulopathy that can be inherited or acquired. Acquired factor X deficiency has been associated with plasma cell dyscrasias, amyloids, and use of vitamin K antagonists. Of plasma cell dyscrasias, most cases in the literature have been associated with multiple myeloma with or without concomitant AL amyloidosis. Here, we present a rare case of acquired isolated factor X deficiency in an elderly patient with immunoglobulin A (Ig A) monoclonal gammopathy of undetermined significance (MGUS). Herein, we highlight a rare cause of acquired factor X deficiency, and we hope to contribute to the growing literature of plasma cell dyscrasias associated with factor X deficiency.